KMnO4/AcOH-mediated C3-selective direct arylation of coumarins with arylboronic acids. Issue 42 (12th April 2016) - Yuan, Jin-Wei; Yang, Liang-Ru; Yin, Qiu-Yue; Mao, Pu; Qu, Ling-Bo
Abstract : An efficient protocol for KMnO4 /AcOH-mediated C3-direct radical arylation of coumarins with arylboronic acids to afford 3-arylcoumarin derivatives is described. Abstract : An efficient protocol for KMnO4 /AcOH-mediated dehydrogenative direct radical arylation of coumarins with arylboronic acids to afford 3-arylcoumarin derivatives is described. A similar reaction system is also applicable to the 3-arylation of quinolinone derivatives. These KMnO4 /AcOH-mediated coupling reactions occur regioselectively at the C3 position of coumarins and quinolinones. Some notable features of this method are high efficiency, moderate to good yield, and a broad group tolerance.